ANALISIS PELAYANAN PUBLIK DALAM PENGURUSAN KARTU IDENTITAS ANAK (KIA) DI KANTOR DESA DAWUHAN KECAMATAN KADEMANGAN KABUPATEN BLITAR - Amanda, Silvana Kissy; Sutowo, Sutowo; Asih W, Ferida (STKIP PGRI Situbondo, 2025)
Quality public services reflect the level of public satisfaction with the services received. This research is motivated by the importance of the Child Identity Card (KIA) as a mandatory population data for children. The purpose of this study was to determine the quality of public services at the Dawuhan Village Office, Kademangan District, Blitar Regency, related to Child Identity Card (KIA) processing services. This study used a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. The analysis was conducted based on the five dimensions of service quality according to Zeithmal, Prasuraman, and Berry (1990): Tangible, Reliability, Responsiveness, Assurance, and Empathy. The results showed that the Tangible dimension had been optimally fulfilled, this can be seen from the availability of facilities and infrastructure that support the service process. The Reliability dimension showed good results through the accuracy and thoroughness of officers in carrying out procedures. The Responsiveness dimension was also good, including the responsiveness and consistency of service from officers. Similarly, in the Assurance dimension, the public generally felt confident in the services provided by officers. The Empathy dimension indicates that communication with the public has been implemented effectively. Given this situation, public services are already quite good and need to be continuously improved to ensure better, more innovative services that meet community needs.